Pathogen-induced damage in Drosophila: Uncoupling disease tolerance from resistance. - Akyaw, P.A.; Paulo, T.F.; Lafuente, E.; Sucena (PLoS Pathogens, 2025)
Immune response against infections can be divided into mechanisms of resistance that ensure active pathogen elimination, and mechanisms of disease tolerance, which include processes that return the host to physiological homeostasis without direct control of pathogen load. Studies on host immune response to infection have targeted mechanisms of resistance, and consequently, these are now well-described in both vertebrates and invertebrates. By comparison, the mechanistic basis of disease tolerance is poorly understood. This is in part because both processes interact and can be difficult to disentangle under an infection scenario. Using the insect model Drosophila melanogaster exposed to its natural entomopathogen, Pseudomonas entomophila, we aimed to tease apart mechanisms of disease tolerance from those of resistance. To this end, we reasoned that the response to oral exposure to heat-killed entomopathogenic bacteria, whilst initially triggering both resistance and disease tolerance mechanisms, would be resolved mainly by disease tolerance alone. Using this method, we observe that oral exposure to heat-killed P. entomophila causes mortality and reduced fecundity in D. melanogaster. We confirm that this reduction in fitness-related traits depends on the duration of the exposure, is sexually dimorphic, and is dependent on the virulence of the bacterium. We also found the microbiota to play a role, with its presence exacerbating the deleterious effect on host survival. In addition, we show that the Imd pathway, but not effector genes, is involved in the process of surviving exposure to HK bacteria. This experimental framework, which may be extended to other systems, can be instrumental towards an understanding of the molecular, genetic, and physiological basis of disease tolerance and its interactions with resistance mechanisms.